Porous silk scaffolds can be used for tissue engineering annulus fibrosus - Chang, G. (Springer-Verlag, 2007)
There is no optimal treatment for symptomatic degenerative disc disease which affects millions of people worldwide. One novel approach would be to form a patch or tissue replacement to repair the annulus fibrosus (AF) through which the NP herniates. As the optimal scaffold for this has not been defined the purpose of this study was to determine if porous silk scaffolds would support AF cell attachment and extracellular matrix accumulation and whether chemically decorating the scaffold with RGD peptide, which has been shown to enhance attachment for other cell types, would further improve AF cell attachment and tissue formation. Annulus fibrosus cells were isolated from bovine caudal discs and seeded into porous silk scaffolds. The percent cell attachment was quantified and the cell morphology and distribution within the scaffold was evaluated using scanning electron microscopy. The cell-seeded scaffolds were grown for up to 8 weeks and evaluated for gene expression, histological appearance and matrix accumulation. AF cells attach to porous silk scaffolds, proliferate and synthesize and accumulate extracellular matrix as demonstrated biochemically and histologically. Coupling the silk scaffold with RGD-peptides did not enhance cell attachment nor tissue formation but did affect cell morphology. As well, the cells had higher levels of type II collagen and aggrecan gene expression when compared to cells grown on the non-modified scaffold, a feature more in keeping with cells of the inner annulus. Porous silk is an appropriate scaffold on which to grow AF cells. Coupling RGD peptide to the scaffold appears to influence AF cell phenotype suggesting that it may be possible to select an appropriate scaffold that favours inner annulus versus outer annulus differentiation which will be important for tissue engineering an intervertebral disc.